Pengaruh Akuntansi Hijau, Tata Kelola, dan Komisaris Independen terhadap Nilai Perusahaan Infrastruktur - Fadilah Novita Dewi; Haryanto Haryanto (Universitas Negeri Padang, 2026)
This study aims to examine how Green Accounting, Corporate Social Responsibility (CSR), and independent commissioners influence the firm value of infrastructure companies listed on the Indonesia Stock Exchange for the 2022–2024 period. The research applies a literature review approach by analyzing company annual reports and sustainability reports. The analysis was conducted using multiple regression based on secondary data obtained. The findings indicate that Green Accounting has a positive and significant effect on firm’s value, while CSR and independent commissioners do not show a positive and significant effect on firm’s value. The results highlight the importance of integrating environmental factors into accounting practices to enhance firm’s value in long-term, especially in sectors with substantial environmental impact such as infrastructure.